Unsupervised deep learning identifies semantic disentanglement in single inferotemporal face patch neurons - Irina Higgins (Nature Portfolio, 2021)
Little is known about the brain’s computations that enable the recognition of faces. Here, the authors use unsupervised deep learning to show that the brain disentangles faces into semantically meaningful factors, like age or the presence of a smile, at the single neuron level.